PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING BERBANTUAN MEDIA QUIZWHIZZER TERHADAP HASIL BELAJAR SISWA KELAS VI PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI MIN 1 PALEMBANG - Zakiah Putri Pratiwi; Muhamad Afandi; Miftahul Husni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low learning outcomes of students in Pancasila Education, as indicated by only 24.14% of students achieving the Minimum Mastery Criteria (KKTP), while 75.86% did not meet the required standard. This condition was attributed to the use of conventional teaching methods that insufficiently engaged students in active learning. Therefore, this study aimed to determine the effect of the Game-Based Learning model assisted by QuizWhizzer media on students’ learning outcomes. This study employed a quantitative approach using an experimental method with a true experimental design in the form of a pretest-posttest control group design. The sample consisted of 58 students divided into an experimental group and a control group. Data were collected through tests and documentation and analyzed using normality tests, homogeneity tests, and hypothesis testing with an independent sample t-test. The results revealed that the mean posttest score of the experimental group (80.68) was higher than that of the control group (65.17). Furthermore, the hypothesis testing showed a significance value of 0.000 < 0.05, indicating that the alternative hypothesis was accepted. In conclusion, the implementation of the Game-Based Learning model assisted by QuizWhizzer media has a significant and effective impact on improving students’ learning outcomes in Pancasila Education.